Pelatihan Dekorasi Cake Di Desa Durin Serugun Kecamatan Sibolangit Kabupaten Deli Serdang - Fitrisna Uliveraty Simamora; Vera Kristina Hutagalung; Susan Rumanti Sitohang; Edward D Panggabean; Melyana Putri (ULINA: Jurnal Pengabdian kepada Masyarakat, 2026)
The purpose of the cake decorating training is to equip participants with the knowledge, technical skills, and creativity to transform ordinary cakes into aesthetically pleasing products and increase their sales value. This increased sales value is expected to equip participants to improve their family income, particularly for the community in Durin Serugun Village, Sibolangit District, Deli Serdang Regency. The training covered an introduction to the tools and ingredients for making cakes and buttercream, basic cake-making techniques, and cake decorating techniques. Each participant's cake decorations were evaluated to provide input on how to improve their skills in creating more attractive cake decorations.